State of the Hypophysis - Thyriod system when being supplied with iodine among the primary school pupils in uplands of Nghe An province - Hung, Tran Ngoc; Hoi, Nguyen Ngoc; Luong, Nguyen Tai (Academia Journal of Biology, 2015)
State of the Hypophysis - Thyriod system when  being supplied with iodine among the primary school pupils in uplands of Nghe An province